EFFECTIVENESS OF DISTANCE LEARNING SYSTEM IMPLEMENTATION AT VOCATIONAL SCHOOL IN BANDA ACEH - Yusran Asnawi; Azizah Lubis; Nurul Fajri; Wiwin Antariyani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
This study aims to analyze the effectiveness of the implementation of the Distance Learning System (DLS) for students at Vocational School in Banda Aceh during the COVID-19 pandemic. This study uses descriptive qualitative methods, with the population of all XII graders from the Software Engineering Department (SED), while the sample is the XII SED 1 class students, totaling 27 students. The instruments of this research are interview questionnaires conducted to 10 teachers of productive subjects and questionnaires distributed to 27 students of class XII SED 1 online using Google Forms. The results showed that many teachers said that the DLS System was not effectively applied in vocational schools, as well as the results of the student response questionnaire that there were many shortcomings in the implementation of DLS. Furthermore, the researchers suggested that the blended learning method be applied to Vocational School